How Vietnamese Organizations Perceive the Use of Social Media in Crisis Communication - Tuong-Minh Ly-Le (Universitas Pelita Harapan, 2019)
Social media has proliferated into the everyday life of Vietnamese people. As a result, in the past years, Vietnam has seen many organizational crises that started on this platform. Social media has proven to be able to foster crises, thanks to open platforms that allow for relatively free discussion among strangers with common interests. Nonetheless, Vietnamese organizations have often ignored or underutilized these channels in their crisis communication efforts. Organizations prioritize using traditional media in their crisis communication efforts and paid little to no attention to social media outlets, even if the crisis had started on social media channels. Through a survey with experienced Vietnamese PR practitioners, this research aims to understand this trend of crisis management and explore the perception of Vietnamese organizations toward the use of social media in crisis communication.Bahasa Indonesia Abstrak: Media sosial telah menjamur ke dalam kehidupan sehari-hari rakyat di Vietnam. Akibatnya, dalam beberapa tahun terakhir, Vietnam telah melihat banyak krisis organisasi yang dimulai pada platform ini. Media sosial telah terbukti mampu menumbuhkan krisis, berkat platform terbuka yang memungkinkan diskusi bebas untuk kepentingan bersama. Meskipun demikian, organisasi di Vietnam sering mengabaikan atau kurang memanfaatkan saluran-saluran ini dalam upaya krisis komunikasi yang mereka alami. Organisasi lebih memprioritaskan menggunakan media tradisional dalam upaya menanggulangi krisis komunikasi mereka dan sedikit memberikan perhatian kepada outlet media sosial, bahkan jika krisis telah dimulai pada saluran media sosial. Melalui survei yang dilakukan oleh praktisi PR di Vietnam yang berpengalaman, penelitian ini bertujuan untuk memahami tren manajemen krisis ini dan mengeksplorasi persepsi organisasi di Vietnam terhadap penggunaan media sosial dalam komunikasi krisis.